Antibiotic resistance and its containment in India. (5th September 2017) - Kakkar, Manish; Walia, Kamini; Vong, Sirenda; Chatterjee, Pranab; Sharma, Anuj
Abstract : Manish Kakkar and colleagues discuss factors contributing to antibiotic resistance in India, and examine policy initiatives to address it